THE MODELING OF AIR POLLUTION WHEN THE LIQUID EVAPORATES FROM THE SOIL - Gunko, Ye. Yu. (Science and Transport Progress, 2007)
The 3D model to simulate the pollutant transfer near building after accidents was developed. The model is based on the transport gradient model and the model of invisid imcompressible fluid. The results of numerical experiments are presented.